Ukrainian Economic Reforms: Current Status And Perspectives In The Face Of Competition On European Union Markets - Greta, Marianna; Pakosz, Mieczysław (Comparative Economic Research. Central and Eastern Europe, 2016)
The conflict in Ukraine since the beginning of 2014 has been the important in the history of Ukraine as an independent state. Despite the danger of economic collapse, the loss of Crimea, and war in its most industrialized region, Ukraine is still trying to conduct reforms and implement Western standards. Through persistent work Ukraine has been moving forward, despite all the difficulties. The society is staying together with the government to save the economy and defend the integrity of the whole country. This article outlines key processes in the Ukrainian reforms during 2014 and describes the cooperation of Ukraine with the European Union and international organizations in the field of financial support and reforms. The main goal of the article is to present the situation in various spheres of the country’s development, but it is also an attempt to present a wider perspective on both the achievements and shortcomings in the process of reforms. The authors focus on those aspects having a significant impact on the Ukrainian economy after February 2014.